(untitled) (The Pakistan Development Review, 2000)
We understand that both the level as well as the composition of investment play a crucial role in the economic development process. However, it needs to be understood that investment contributes to the growth process by increasing the productive capacity, improving the technology, and enhancing the competitiveness of an economy. And when it is supplemented with investment in the social sectors, it also results in human development. The demand for investment depends on strong macroeconomic fundamentals comprising stability of exchange rates, fiscal prudence, feasible structure of financial market, including the regulatory and supervisory framework and the size and quality of the securities and bond markets, and continuity of a consistent investment policy.